Host genetic polymorphisms and serological response against malaria in a selected population in Sri Lanka - Dewasurendra, RL; Jeffreys, A; Gunawardena, SA; Chandrasekharan, NV; Rockett, K; Kwiatkowski, D; Karunaweera, ND (BioMed Central, 2018)
Background: Antibodies against the merozoite surface protein 1-19 (MSP1-19) and the apical membrane antigen 1 (AMA1) of the malaria parasite (Plasmodium vivax) are proven to be important in protection against clinical disease. Diferences in the production/maintenance of antibodies may be due to many factors including host genetics. This paper discusses the association of 4 anti-malarial antibodies with selected host genetic markers. Methods: Blood was collected from individuals (n=242) with a history of malaria within past 15 years for DNA and serum. ELISA was carried out for serum to determine the concentration of anti-malarial antibodies MSP1-19 and AMA1 for both vivax and falciparum malaria. 170 SNPs related to malaria were genotyped. Associations between seropositivity, antibody levels and genetic, non-genetic factors were determined. Results: Age ranged 13–74 years (mean age=40.21 years). Majority were females. Over 90% individuals possessed either one or more type(s) of anti-malarial antibodies. Five SNPs were signifcantly associated with seropositivity. One SNP was associated with MSP1-19_Pv(rs739718); 4 SNPs with MSP1-19_Pf (rs6874639, rs2706379, rs2706381 and rs2075820) and1 with AMA1_Pv (rs2075820). Eleven and 7 genotypes (out of 15) were signifcantly associated with either presence or absence of antibodies. Three SNPs were found to be signifcantly associated with the antibody levels viz. rs17411697 with MSP1-19_Pv, rs2227491 with AMA1_Pv and rs229587 with AMA1_Pf. Linkage of the markers in the two groups was similar, but lower LOD scores were observed in seropositives compared to seronegatives. Discussion and conclusions: The study suggests that several SNPs in the human genome that exist in Sri Lankan populations are signifcantly associated with anti-malarial antibodies, either with generation and/or maintenance of antibodies for longer periods, which can be due to either individual polymorphisms or most probably a combined efect of the markers.